O-P01 Potential Utility of Intraoperative Fluid Amylase Measurement During Pancreaticoduodenectomy. (16th December 2021) - Joshi, K; Abradelo, M; Chatzizacharias, N; Bartlett, D; Dasari, B; Isaac, J; Marudanayagam, R; Mirza, DF; Roberts, K; Sutcliffe, RP
Abstract: Background: Postoperative pancreatic fistula (POPF) after pancreaticoduodenectomy (PD) is a source of major morbidity and mortality. Early diagnosis and treatment of POPF is mandatory to improve patient outcomes, and clinical risk scores may be combined with postoperative drain fluid amylase (DFA) values to stratify patients. The aim of this study was to determine if intraoperative fluid amylase values (IFA) correlate with DFA1 and POPF. Methods: In consecutive patients undergoing PD between February and November 2020, intraoperative samples of intra-abdominal fluid adjacent to the pancreatic anastomosis were taken and sent for fluid amylase measurement prior to abdominal closure. Data regarding patient demographics, postoperative DFA values, complications and mortality were prospectively collected. Results: Patient Demographics: Data was obtained for 52 patients with a median alternative Fistula Risk Score (aFRS) of 9.4. Postoperative complications occurred in 20 patients (38%), including five Clavien grade 3+. There were eight POPFs and two patients died (pneumonia/sepsis). There was significant correlation between IFA and DFA1 (Pearson's correlation: R 2 =0.713; p < 0.001) and DFA3 (p < 0.001), and median IFA was higher in patients with POPF than patients without (1232.5 vs. 122; p = 0.0003). IFA>260 U/l predicted POPF with sensitivity, specificity, PPV and NPV of 88%, 75%, 39% and 97%, respectively. The incidence of POPF was 43% in high risk (high aFRS/IFA) and 0% in low risk patients (low aFRS/IFA). Complications: Conclusions: Intraoperative fluid amylase closely correlated with postoperative pancreatic fistula, and may be a useful adjunct to clinical risk scores to stratify patients during pancreatico-duodenectomy, allowing targeted intervention to reduce the clinical impact of pancreatic fistula.It is possible to detect fluid amylase adjacent to the completed pancreatic anastomosis in patients undergoing PD. Presence of IFA correlates with postoperative DFA and POPF. IFA increases the accuracy of the alternate Fistula Risk Score in predicting POPF. Low risk patients with a low IFA may be suitable for a 'no drain' strategy, whilst patients with a high IFA may benefit from intraoperative mitigation strategies to reduce the incidence and/or severity of a postoperative pancreatic fistula.